Self‐Care Dependency Evaluation Form: Psychometric properties of the revised version with 27 items - Parente, Paulo; Costa, Andreia; Pereira, Soraia; Puga Machado, Paulo Alexandre; Martins, Teresa; Pereira, Filipe Miguel Soares; Silva, Abel (wiley, 2021)
Abstract Introduction: The Self-Care Dependency Evaluation Form assesses dependency in performing self-care activities, but its original version is extensive and provides redundant information. The present study aims to scrutinise the items of the scale with the purpose of creating a revised version and to evaluate its psychometric properties. Methods: The study was conducted in two phases. In the first phase, an exploratory and correctional analysis of the items of the original form was performed from a database with 282 participants, followed by a review by a panel of experts who analysed the discriminatory ability and the contribution and relevance of each item, which resulted in the revised version. In the second phase, a new study with a sample comprising 150 participants was conducted to test the psychometric properties of the revised version. All ethical aspects and matters of confidentiality and privacy were assured. Results: The scale with 27 items shows good internal consistency, ranging from 0.67 (taking medication) to 0.96 (walking). It was moderately correlated with the Barthel Index and the Lawton and Brody Scale, proven to be a discriminatory measurement instrument. Discussion/Conclusion: This measure will enable health professionals to better evaluate self-care activities and provide more efficient, simple and effective prescriptions.
Keywords: Quantitative approaches; Instrument development; Gerontology